Determination of Cadmium Levels in Agricultural Soils of Some Regions in Syria - Ranim Ibrahim; Sophie Barguil; Sondos Hesenow (Universitas Gadjah Mada, 2023)
Soil pollution with heavy metals has become a serious global threat, largely due to anthropogenic activities, and cadmium (Cd) is one of the most toxic known heavy metals. This study aimed to assess cadmium levels in several agricultural soils in several Syrian regions. Soil samples were taken from six agricultural lands, prepared, and processed to determine the total content of cadmium using a graphite furnace atomic absorption spectrometry. The results showed that the values of cadmium concentration ranged between 0.60 and 1.48 ppm in the studied soil samples, exceeding the permissible limit in some areas. Cadmium values were higher in farmland soils near industrial facilities than those far from them. This study indicates the spread of Cd contamination throughout the study area, significantly near the industrial activities; thus, it may impact local agricultural production safety and human health.